Dynamic theory of the relativistic electron radiation in periodic layered medium in Laue geometry - Blazhevich, S.V.; Gladkih, Ju.P.; Noskov, A.V. (Вопросы атомной науки и техники, 2013)
A theory of coherent X-ray radiation of a relativistic electron crossing the artificial periodic medium in the Laue scattering geometry is constructed. The expressions describing the spectral and angular characteristics of radiation in the direction of Bragg scattering are obtained and investigated. By analogy with the radiation emission in a crystalline medium this radiation is considered as the result of coherent summation of the contributions of two radiation mechanisms: parametric (PXR) and diffracted transition (DTR). It is shown that the yield of DTR from layered target can be more than one order higher than the yield in single crystal radiator, under similar conditions. The manifestations of the Borrmann effect for DTR in the artificial multilayer environment are demonstrated for a Laue scattering geometry.